Features of the Family Model of Corporate Management in China - Yi Wang; Victoria Chernova (Communications of International Proceedings, 2021)
Chinese government views the development of domestic enterprises as a general incentive for economic growth, for recovery of the market and increasing opportunities for employment. In last 20 years small and medium enterprise sector, as well as big business and corporations became indispensable part of Chinese economy and now are creating jobs and are developing more and more of innovation technologies.  In the XXI century China managed to significantly strengthen its strategic positions in global economy and began to ore significantly influence the nature and trends of the development of global economy in general. Meanwhile the basic model of management in every organization in China is the family model of corporate management, which is the main factor of China economy success. The main goal of this thesis is examination of specificities, features, challenges, and growth prospects of the China family model of corporate management.
Keywords: Entrepreneurship; family business; business development strategies; national management; business culture; mentality features